Evaluación de la calidad espermática porcina sometida a los distintos niveles de coenzima Q10 y vapor de nitrógeno durante la congelabilidad - Buste Alcívar, Cristhian Damián (2022)
The present study consisted of evaluating the quality of boar semen subjected to different levels of coenzyme Q10 at different levels of nitrogen vapor during freezability. For this purpose, an experimental trial with DBCA design with analysis of variance was implemented, previously the assumptions of normality of the data (Shapiro-wilks) and homogeneity of variances (Bartlett) and the Tukey test were verified to establish the level of significance of the results through statistical package InfoStat version 2017. The effect of coenzyme Q10 (0.04 and 0.06mg/mL) was measured. and cryopreservation with nitrogen vapor (5cm, 10cm, 15cm); the variables evaluated were vitality, mortality and semen motility; Normal-damaged apical edge, proximal-distal cytoplasmic droplet and cost- benefit ratio. The results indicate highly significant statistical differences for the semen vitality variable (p<0.0001), semen mortality (p<0.0001) and the damaged apical edge variable (p<0.0001); there were no statistical differences for the rest of the variables. In economic terms, all treatments generated economic losses when analyzing the production of 1000 straws for each treatment. Cryopreservation does not represent an appropriate method due to the structural and functional alterations developed during temperature changes after freezing and thawing of semen, which is why its use is not suggested commercially.